Generation, localization and functions of macrophages during the development of testis - Emmi Lokka; Laura Lintukorpi; Sheyla Cisneros-Montalvo; Juho-Antti Mäkelä; Sofia Tyystjärvi; Venla Ojasalo; Heidi Gerke; Jorma Toppari; Pia Rantakari; Marko Salmi (NATURE PUBLISHING GROUP, 2022)
In the testis, interstitial macrophages are thought to be derived from the yolk sac during fetal development, and later replaced by bone marrow-derived macrophages. By contrast, the peritubular macrophages have been reported to emerge first in the postnatal testis and solely represent descendants of bone marrow-derived monocytes. Here, we define new monocyte and macrophage types in the fetal and postnatal testis using high-dimensional single-cell analyses. Our results show that interstitial macrophages have a dominant contribution from fetal liver-derived precursors, while peritubular macrophages are generated already at birth from embryonic precursors. We find that bone marrow-derived monocytes do not substantially contribute to the replenishment of the testicular macrophage pool even after systemic macrophage depletion. The presence of macrophages prenatally, but not postnatally, is necessary for normal spermatogenesis. Our multifaceted data thus challenge the current paradigms in testicular macrophage biology by delineating their differentiation, homeostasis and functions. The developmental origins and functions of testis macrophages remain incompletely characterized. Here, the authors show, using histology, high-dimensional mass cytometry and cell fate-mapping data, that interstitial and peritubular macrophages originate from distinct precursors and contribute distinctly to spermatogenesis.